PROSES PENYUSUNAN ANGGARAN & PENGALOKASIAN BELANJA DI PEMDA KABUPATEN WONOGIRI - Fadillah, H.M. Nuh; Muhtar, Muhtar (Journal of Indonesian Economy and Business, 2004)
This study evaluates the budget formulation process of Wonogiri regency, includingefforts to accommodate public aspiration and the roles of local parlement.The information used are secondary and primary data. Secondary data are Income andLocal Budget, consist of incomes (local income, balancing fund and various legal incomes),expenditures (expenditure for local apparatus and expenditure for public services) eachconsists of general administrative expenditure, maintenance and operational budget, andcapital/ investment expenditure) and funding (i.e. local income and local spending).Primary data were observation results conducted during budget meetings, interviews withthe head of budget division and the head of C Commission of local parlement. Analysisinstruments employed were qualitative-descriptive and proportional analysis.Keywords: budget formulation process, qualitative descriptive and proportional analysis,criteria of performance budget formulation, planning programming andbudgeting system.